2016
DOI: 10.1039/c6py01759b
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and chiroptical properties of a π-conjugated polymer containing glucose-linked biphenyl units in the main chain capable of folding into a helical conformation

Abstract: Naturally occurring ellagitannins provide us with inspiration for the development of a chiral π-conjugated polymer bearing glucose-linked biphenyl units in the main chain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 52 publications
(2 reference statements)
0
27
0
Order By: Relevance
“…Ikai's group polymerized thiophene with glucose-linked biphenyl units to afford a series of copolymers 36 with axial chirality. [59][60][61] All the copolymers exhibited CD and CPL signals in both solution and films indicating a helix structure of a single polymer chain. With the decrease of the thiophene rings, the structure irregularity due to the rotation of the C-C bond between thiophene rings reduced; as a result, less repeating units were needed to stabilize the helical structure of the polymer chain.…”
Section: Chirality Introduced By Substituents With Planar or Axial Chiralitymentioning
confidence: 96%
“…Ikai's group polymerized thiophene with glucose-linked biphenyl units to afford a series of copolymers 36 with axial chirality. [59][60][61] All the copolymers exhibited CD and CPL signals in both solution and films indicating a helix structure of a single polymer chain. With the decrease of the thiophene rings, the structure irregularity due to the rotation of the C-C bond between thiophene rings reduced; as a result, less repeating units were needed to stabilize the helical structure of the polymer chain.…”
Section: Chirality Introduced By Substituents With Planar or Axial Chiralitymentioning
confidence: 96%
“…Inspired by the sophisticated functions of biological helical polymers and their assemblies, a rich variety of artificial helical polymers has been prepared over the past decades in order to develop advanced chiral materials for the resolution of enantiomers by chromatography, sensing of chiral molecules, and circularly polarized luminescence . The application of optically active helical polymers for asymmetric catalysis has also attracted growing interest, because a one‐handed helical chirality can significantly contribute to the enantioselectivity due to a one‐handed helical arrangement of the catalytically active, chiral/achiral units along the one‐handed helical polymer backbone .…”
Section: Introductionmentioning
confidence: 99%
“…Previously, the intensive excimer emission of 10 -5 M solutions of compound 1 in methylcyclohexane was reported [32]. Based on the earlier reports [34,35], we suggested that the polarity of a solvent can be the driving force for the geometry changes in the molecule of 1, which are highly soluble in non-polar solvents. In polar solvent media, this lipophilic molecule could act as a surfactant and the hydrophobic interactions would make molecule 1 to bend over the pentane linker.…”
Section: Resultsmentioning
confidence: 79%
“…Fig. 1 Synthetic scheme for sensor 1 However, in our experiments only a feeble response through the excimer fluorescence quenching with poor linearity in the Stern-Volmer plot was observed in cyclohexane.Based on the earlier reports[34,35], we suggested that the polarity of a solvent can be the driving force for the geometry changes in the molecule of 1, which are highly soluble in non-polar solvents. In polar solvent media, this lipophilic molecule could act as a surfactant and the hydrophobic interactions would make molecule 1 to bend over the pentane linker.…”
mentioning
confidence: 92%